Penggunaan Model Pembelajaran Discovery Learning dalam Pembinaan Akhlakul Karimah pada Santri Pesantren Terpadu Nurul Islam Blang Rakal - Sulman, Sulman (Pase: Journal of Contemporary Islamic Education, 2022)
This research focuses on the moral building of students (santri) in Integrated Pesantren of Nurul Islam Integrated. The purpose of this study is to explain the use of the Discovery Learning model and the constraints encountered in using the Discovery Learning learning model and to describe the The students moral building through the learning system. This study uses qualitative research by using a pedagogic approach. Data obtained through observation, interviews, and document study. The results of this research are: 1) The learning process in class is no longer focused on the teacher as the main source of knowledge but the role of students is also very good. 2) The use of the Discovery Learning model at the Nurul Islam Integrated Pesantren Nurul Iman is carried out in several steps, namely: stimulus, problem statement, data collection, data processing, and verification. 2) The obstacles encountered in using the Discovery Learning model are: the process of forming groups for students takes a long time, students find it difficult to identify problems. 3) The The students moral building at Integrated Pesantren of Nurul Islam Blang Rakal use the individual and classical system.